2010
DOI: 10.1002/jcb.22640
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the mechanisms of osteoclast precursor fusion

Abstract: Bone marrow macrophages fuse on the bone surface to form multinucleated osteoclasts that then organize to efficiently resorb bone. Many, if not all, of the stages of macrophage fusion involve cytoskeletal components that reorganize the cells. Recruitment may involve chemotactic responses to bone matrix protein and calcium ion gradients and/or chemokine production by bone forming osteoblasts. The roles of integrins vary, depending on the particular subunits with some interfering with fusion and others having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…Many surface receptors including DC-STAMP and MFR/SIRPα, are critical for fusion from mononucleated precursors into multinucleated cells. In addition, ADAM8 and ADAM12 which are disintegrins/metalloproteinases secreted prior to fusion, may be affected in this model (Oursler, 2010). Calcitonin, the ligand for CTR, is responsible for lowering calcium levels in the blood by inhibiting bone resorption by inducing morphological changes leading to osteoclast retraction (Naot and Cornish, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many surface receptors including DC-STAMP and MFR/SIRPα, are critical for fusion from mononucleated precursors into multinucleated cells. In addition, ADAM8 and ADAM12 which are disintegrins/metalloproteinases secreted prior to fusion, may be affected in this model (Oursler, 2010). Calcitonin, the ligand for CTR, is responsible for lowering calcium levels in the blood by inhibiting bone resorption by inducing morphological changes leading to osteoclast retraction (Naot and Cornish, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, osteoclast precursor motility is required for cell-cell interaction, leading to subsequent differentiation and fusion (Fujita et al, 2012;Oursler, 2010). We therefore investigated whether ActA altered pre-osteoclast motility using time-lapse video microscopy of OCL precursors plated on both plastic and bovine bone.…”
Section: Activin a Decreases The Motility Of Mbmm Precursorsmentioning
confidence: 99%
“…18,19) Of the multiple candidate factors, we next focused on DC-STAMP and ATP6v0d2 because both factors have been reported to be involved in osteoclast fusion 16) and are downstream of NFATc1, a master transcription factor for osteoclastogenesis. 20) Using RT-PCR, we found that the levels of NFATc1, TRAP, and DC-STAMP expression in RAW-ISG cells in response to RANKL treatment were somewhat higher than those in RAWMock cells under the same conditions (Fig.…”
Section: Isg15 Suppresses Atp6v0d2mentioning
confidence: 99%